2020
DOI: 10.2147/orr.s215742
|View full text |Cite
|
Sign up to set email alerts
|

<p>Functional Outcomes Following Surgical Fixation of Paediatric Lateral Condyle Fractures of the Elbow – A Systematic Review</p>

Abstract: Objective: Lateral humeral condyle fractures are the second most common elbow fractures in children. Both K-wire fixation and screw fixation have been advocated as suitable treatment options for displaced fractures. This study aimed to identify which fixation method was associated with the best functional outcomes. Methods: A systematic review was conducted. Studies reporting functional outcomes following surgical fixation of lateral condyle fractures were included for review. The primary outcome measure was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…However, the authors found that K-wires had less capacity to compress and retain the fragments in place. In a systematic review, Birkett et al [5] found that the highest rates of excellent functional outcome were seen with lag screw fixation (95%) compared to K-wire fixation (83.3%), but the results were comparable between two groups.…”
Section: Functional Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…However, the authors found that K-wires had less capacity to compress and retain the fragments in place. In a systematic review, Birkett et al [5] found that the highest rates of excellent functional outcome were seen with lag screw fixation (95%) compared to K-wire fixation (83.3%), but the results were comparable between two groups.…”
Section: Functional Outcomementioning
confidence: 99%
“…The optimal method of fixation for maintaining reduction is still debated [4]. In a systematic review of ten retrospective comparative studies [5], no firm conclusions Inclusion criteria were lateral condyle fractures of humerus with more than 2 mm displacement, between 5 to 12 years of age and less than 2 weeks duration since injury. Exclusion criteria were fractures associated with ipsilateral humerus or forearm fractures and children with bicondylar fractures or comminuted fractures of the distal humerus and lateral condyle fractures with a small metaphyseal fragment.…”
Section: Introductionmentioning
confidence: 99%
“…Good results have been reported with both K-wires and screw fixation for LCHF in the literature [7,13,24,33,34,35,36]. Recent studies have favoured screw fixation over K-wires due to reduced cast time, earlier mobilisation, reduced infection rates, fewer non-union rates, faster time to union due to compression at fracture site and overall better motion at follow up [7,13,24,27,33,34].…”
Section: Screws Vs Pinsmentioning
confidence: 99%